Recurrence rate of basal cell carcinoma in patients submitted to skin flaps or grafts - Rogerio Nabor Kondo; Airton dos Santos Gon; Rubens Pontello Junior (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Basal cell carcinoma is the most common type of skin cancer. Although the literature provides a great deal of information on the recurrences of basal cell carcinoma, studies about these indices addressing only the cases in which flaps and/or grafts have been performed for surgical reconstruction of the excision of this tumor are still lacking. Objectives: To evaluate rates of recurrence of basal cell carcinoma submitted to conventional surgery with pre-established margins and reconstruction by flaps or grafts. Methods: A retrospective and observational study was performed through the analysis of 109 patients, who met inclusion criteria with 116 basal cell carcinomas submitted to conventional surgery and pre-established safety margins, requiring reconstruction through a graft or cutaneous flap. This work was performed the small surgeries sector of Dermatology of the Specialty Outpatient Clinic of the University Hospital of the State University of Londrina, between January 1, 2011 and December 31, 2015. The following data were collected and inserted in an Excel worksheet: name, registration number of the hospital patient, sex, age, tumor location, histopathological type of BCC, procedure performed (type of flap and/or graft), follow-up time, recurrence. Results: Of the 116 procedures, there were recurrences in 3 cases (2.6%) that were located in the nasal region and related to sclerodermiform or micronodular histological types. Study limitations: Retrospective nature of the study. Conclusion: The present study of the dermatology department of this university hospital showed a low rate of recurrence of basal cell carcinoma in cases where flaps and/or grafts were used in the surgical reconstruction.